Numerical Analysis on the Sub-Span Oscillation of Iced Eight-Bundle Conductors During Galloping - Yu, Liu; Mengqi, Cai; Qingyuan, Wang; Linshu, Zhou; Qian, Xu; Shunli, Ding; Jun, Liu; Chunlin, Huang (Frontiers in Energy Research, 2022)
Under the excitement of wind loads, UHV transmission lines are subject to two types of vibration phenomena, namely, sub-span oscillation and galloping. This phenomenon can easily lead to conductor breakage, interphase flashover, fatigue damage to fittings, and even lead to tower collapse and disconnection accidents. The numerical analysis method is used to analyze the sub-span oscillation characteristics of the eight-bundle conductor during galloping. The results of the numerical simulation are compared to explore the influence of wind speed, span length, initial angle of wind attack and turbulence intensity on the galloping line, looking for movement characteristics between each sub-conductor. The results provide reference for the research on galloping principle of UHV transmission line and anti-oscillation, so as to further improve the resistance of the power grid against disasters ability.